A critical review based on Fault Tolerance in Software Defined Networks - Shailly , Ms. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
SDN (Software-Defined Networks) is an incipient architecture of decoupling control plane and data plane involved in dynamic management of network. SDN is being installed in production based networks which ultimately lead to the need of secure and fault tolerant SDN. In the present investigation, we are discussing about the kind of failures with label happen in SDN. A critical survey based on the recently proposed mechanisms for handling failures in SDN. Initially, we discussed with the help of tabular data involving mechanism of data plane failure. We also discussed the various mechanisms for handling misconfiguration of drift able of switches and control plane failure handling mechanisms. We also epitomize issues with both data and control plane mechanism that are discussed earlier. In the end, we are stating that there is need of build much efficient and secure mechanism for SDN networks.